Possession Rights over Reclaimed Land: A Legal Analysis of Foreign Legal Entities Ownership Status - Suganda, Yosua Simon (Walisongo Law Review (Walrev), 2023)
Rapid population growth without a corresponding increase in land availability can lead to issues such as a significant long-term rise in land prices. Reclamation emerges as an option to assist communities in obtaining land at affordable prices. However, the implementation of reclamation must adhere to the terms and regulations set by the government, including provisions related to foreign legal entities intending to engage in reclamation activities. This article employs a normative juridical approach and juridical analysis methods. The findings indicate that foreign legal entities can undertake reclamation activities by legal requirements governing individual and corporate legal entities, whether local or foreign, provided they have obtained reclamation permits. Foreign legal entities are allowed to have land rights in the reclaimed area, but the land status is in the form of usage rights and lease rights after obtaining permission from the government. In conclusion, implementing reclamation by foreign legal entities necessitates compliance with applicable regulations and requirements to ensure the sustainability and success of these activities. Pertumbuhan penduduk yang cepat tanpa disertai peningkatan luas lahan dapat menimbulkan masalah, seperti kenaikan harga tanah yang signifikan dalam jangka panjang. Reklamasi menjadi opsi untuk membantu masyarakat memperoleh tanah dengan harga terjangkau. Namun, pelaksanaan reklamasi harus mematuhi syarat dan ketentuan pemerintah, termasuk ketentuan terkait subjek hukum asing yang ingin melakukan kegiatan reklamasi. Artikel ini menggunakan pendekatan yuridis normatif dan metode analisis yuridis. Hasil kajian menunjukkan bahwa subjek hukum asing dapat melakukan reklamasi sesuai dengan persyaratan hukum yang mengatur subjek hukum baik perorangan maupun badan hukum, baik lokal maupun asing, asalkan telah memperoleh izin reklamasi. Untuk subjek hukum asing, diperbolehkan memiliki hak atas tanah reklamasi, namun status tanahnya berupa hak pakai dan hak sewa setelah mendapatkan izin dari pemerintah. Kesimpulannya, penerapan reklamasi oleh subjek hukum asing memerlukan ketaatan terhadap regulasi dan persyaratan yang berlaku untuk memastikan keberlanjutan dan keberhasilan kegiatan tersebut.